2015
DOI: 10.5114/pg.2014.47502
|View full text |Cite
|
Sign up to set email alerts
|

The aberrant overexpression of vimentin is linked to a more aggressive status in tumours of the gastrointestinal tract

Abstract: Vimentin is an intermediate filament protein normally expressed in cells of mesenchymal origin, e.g. myofibroblasts, chondrocytes, macrophages, and endothelial cells. The expression of vimentin, which has been thought of as the main mesenchymal marker, is also detected in tumour tissue. In tumours of the gastrointestinal tract vimentin expression is usually correlated with advanced stage of tumour, lymph node metastasis, and patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…We examined the expression levels of vimentin and USP14 in our GC sample cohorts by RT-qPCR and found higher expression levels in cancer compared with the paired adjacent normal tissues (Figures 1A and 5A ). The GC cells yielded similar results (Figure 1B and Figure S2E ), which were consistent with previous studies [ 4 , 21 , 22 , 29 – 33 ]. The correlation analysis between USP14 and vimentin in GC tissues revealed their positive correlations (Figure 5B ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We examined the expression levels of vimentin and USP14 in our GC sample cohorts by RT-qPCR and found higher expression levels in cancer compared with the paired adjacent normal tissues (Figures 1A and 5A ). The GC cells yielded similar results (Figure 1B and Figure S2E ), which were consistent with previous studies [ 4 , 21 , 22 , 29 – 33 ]. The correlation analysis between USP14 and vimentin in GC tissues revealed their positive correlations (Figure 5B ).…”
Section: Resultssupporting
confidence: 92%
“…Large quantities of evidence have shown that vimentin is upregulated in GC tissues [ 4 ], but the underlying mechanism of its upregulation is still unclear. The following factors were confirmed to modulate vimentin expression: (1) non-coding RNA in the regulation of transcription, such as miR-135a, miR-137, miR-200c, miR-141, miR-122 and long non-coding RNA [ 5 11 ]; (2) protein modification, such as phosphorylation and acetylation [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The contraction of myosin, the polymerization of actin, and cell adhesion could all affect cell migration (Head et al, 2014;Kevenaar and Hoogenraad, 2015). The intermediate filaments in the cytoskeletal structures play an important role in the maintenance and regulation of cell function, such as cell contraction, migration, proliferation, gene expression, and apoptosis (Eriksson et al, 2004;Xu and Yan, 2009;Brzozowa et al, 2015). Regarding cytoskeleton-associated proteins, Krause's review concludes that the VASP protein is a regulators of the actin cytoskeleton and cell migration (Krause et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The intermediate filament protein vimentin is the major cytoskeletal protein in mesenchymal cells and has become one of the most widely used markers of EMT 21 correlating with the relatively aggressive proliferative and migratory activity of cells during embryogenesis and cancer metastasis. [36][37][38]79,[108][109][110] In the absence of vimentin, migration is significantly reduced. 39 Thus the E-cadherin/vimentin ratio determines the switch from low to high invasion capacity.…”
Section: Vimentinmentioning
confidence: 99%
“…35 Vimentin is a microtubular component involved in the regulation of cytoskeletal function relevant to the changes in intercellular adhesion and EMT. [36][37][38][39] The expression of vimentin is increased as cells lose adherence and transition from a resting, epithelial phenotype to a migratory behaviour.…”
Section: Introductionmentioning
confidence: 99%